Determination of iodine value of palm oil by fourier transform infrared spectroscopy - Che Man, Y. B.; Setiowaty, G.; van de Voort, F. R. (Wiley, 1999)
A rapid method for the quantitative determination of iodine value (IV) of palm oil products by FTIR transmission spectroscopy is described. A calibration standard was developed by blending palm stearin and superolein in specific ratios that covered a range of 27.9 to 65.3 IV units. The spectra of these standards was measured in the range between 3050 and 2984 cm−1, corresponding to the absorption band of=C-H cis stretching vibration. A partial least squares calibration model for the prediction of IV was developed to quantify the IV of palm oil products. A validation approach was used to optimize the calibration with a correlation coefficient of R2=0.9995 and a standard error of prediction of 0.151. This study concludes that the FTIR transmission approach can be used to determine the IV of palm oil products with a total analysis time per sample of less than 2 min for liquid samples.